Análisis del plan de gestión integral de residuos sólidos de la ciudad de Bogotá para el periodo 2019- primer semestre. - Munar Caicedo, Geraldine (Universidad Antonio Nariño, 2021)
The generation of solid waste in the capital is one of the main environmental problems in Bogotá, since it is not being treated properly and the generation is exceeding the capacity and the landfill does not have enough capacity to store it in its entirety in addition to what we receive from 6 more municipalities. The present document consisted in developing an analysis of the solid waste plan of the city of Bogotá in the first semester of the year 2019 in which it was possible to identify which wastes are being generated in greater quantity, which treatment can be carried out on those wastes and currently which is their final disposal. As a first part of the work, a visit to the recycling warehouse of the farm, administered by the district, is made in order to know its administration, how is the handling of the waste, what machinery it has and the capacity of the waste that they receive, then it is determined according to the amount generated and used, to analyze according to the applicable regulations for the elaboration of this management plan, additionally a diagnosis of the current composting in the entity is established through a survey to the personnel in charge of the handling of this process; Then, the criteria of the strategic plans were defined and the main deficiencies were determined. This analysis is carried out according to the research carried out, the applicable regulations, and the interview conducted during the visit to the winery.